A novel comparative study for electrochemical urea biosensor design: Effect of different ferrite nanoparticles (MFe2O4, M: Cu, Co, Ni, Zn) in urease immobilized composite system - Sanko, Vildan; Senocak, Ahmet; Tumay, Sureyya Oguz; Demirbas, Erhan (Elsevier Science Sa, 2023)
A new enzymatic electrochemical biosensor has been developed with the PANI/Nafion composite system con-taining ferrite nanoparticles with four different transition metals. The ferrite nanoparticles containing copper, cobalt, nickel, and zinc metals were synthesized by the co-precipitation method and their surfaces were modified with tetraethoxysilane and (3-aminopropyl) triethoxysilane to obtain -NH2 function in order to develop the purposed sensing system. The modified and unmodified ferrite nanoparticles were characterized by physically, chemically, and morphologically. Ferrite nanoparticles with suitable for enzyme immobilization were integrated on the GCE surface and covered with PANI/Nafion. According toelectrochemical measurements, it was deter-mined that copper ferrite nanoparticles, which have the lowest bandgap value, significantly increased the biosensor performance. Cyclic voltammetry (CV) and differential pulse voltammetry (DPV) were used to monitor biosensor production and evaluate its performance. A detection limit of 0.17 mu M and a wide linear range of 0.5-45.0 mu M were obtained for the urea detection with the DPV method with the sensing system (Nf/PANI/CuF/ Urs). The biosensor has been successfully applied to soil and milk samples with high accuracy. In addition, it has been determined that the proposed method has good reproducibility, selectivity, and stability.
Keywords: Urea detection; Biosensor; Ferrite nanoparticles; Electrochemical sensing; conductive polymer